Smart City Based Economic Development by Integrating Technology for Urban Welfare in Makassar City - Rahman, Abdul (Newinera Publisher, 2023)
This study investigates the impact of smart city initiatives on economic development and urban welfare in Makassar City using a quantitative approach. Employing a stratified random sampling technique, data were collected from 400 respondents, including residents, government officials, and business entities, through a structured questionnaire. Analysis using Pearson correlation, multiple regression, t-tests, ANOVA, and ANCOVA revealed significant positive correlations between smart city initiatives and both economic development and urban welfare. The findings demonstrate that smart city projects significantly contribute to job creation, business growth, and improved quality of life, with variations in perceptions across different stakeholder groups and demographic categories. This research addresses gaps in the literature by providing localized insights into the effects of smart city interventions in a developing city context and offers actionable recommendations for policymakers and urban planners.